The Asgard archaeal origins of Arf family GTPases involved in eukaryotic organelle dynamics - Vargová, Romana; Chevreau, Roxanne; Alves, Marine; Courbin, Camille; Terry, Kara; Legrand, Pierre; Eliáš, Marek; Ménétrey, Julie; Dacks, Joel B; Jackson, Catherine L (Nature microbiology, 2025)
The evolution of eukaryotes is a fundamental event in the history of life. The closest prokaryotic lineage to eukaryotes, the Asgardarchaeota, encode proteins previously found only in eukaryotes, providing insight into their archaeal ancestor. Eukaryotic cells are characterized by endomembrane organelles, and the Arf family GTPases regulate organelle dynamics by recruiting effector proteins to membranes upon activation. The Arf family is ubiquitous among eukaryotes, but its origins remain elusive. Here we report a group of prokaryotic GTPases, the ArfRs, which are widely present in Asgardarchaeota. Phylogenetic analyses reveal that eukaryotic Arf family proteins arose from the ArfR group. Expression of representative Asgardarchaeota ArfR proteins in yeast and X-ray crystallographic studies show that ArfR GTPases possess the mechanism of membrane binding and structural features unique to Arf family proteins. Our results indicate that Arf family GTPases originated in the archaeal ancestor of eukaryotes, consistent with aspects of the endomembrane system evolving early in eukaryogenesis.
Keywords: organely; Saccharomyces cerevisiae; Crystallography, X-Ray; Phylogeny; Eukaryotic Cells; Eukaryota; krystalografie rentgenová; archeální proteiny; Organelles; molekulární evoluce; Evolution, Molecular; GTP Phosphohydrolases; Archaeal Proteins; Archaea; eukaryotické buňky; fylogeneze; GTP-fosfohydrolasy